THE ANALYSIS OF OVERPRESSURE GENERATING MECHANISM AND PORE PRESSURE PREDICTION IN WOKAM BLOCK AREA ARU BASIN - SHIMA (NIM: 22014303), JOSHUA
The Aru Field is a hydrocarbon basin located in Papua. Some exploration wells in this field show the presence of overpressure condition, causing some obstacle during the drilling. This research aims at analysing the generating mechanism of overpressure in relation with the geologic condition in this basin. This research is performed by using 6 wells located on onshore and offshore. The result of the analysis shows that overpressure in the study area is caused by both loading and non loading (hydrocarbon generation) mechanisms. The calculation of burial rate shows that the burial rate of Buru Formation interval in Bumerah-1X is 444.5 m/Ma, and this burial is thought to be the generating mechanism of overpressure by loading mechanism. Meanwhile, cross plot of Ro and Tmax shows that hydrocarbon generation occurs at Piniya Formation interval, and it contributes to overpressure generating mechanism with non loading mechanism as observed at Kola-1X. The distribution of overpressure zone based on seismic velocity map shows that the overpressure in Buru and Piniya formations is distributed in the northwestern, southern, and eastern parts of the study area. The pore pressure prediction by applying Eaton’s method shows that low overpressure magnitude could be estimated by applying the Eaton’s exponent of 1.2. Meanwhile, for high overpressure magnitude, the Eaton’s exponent is 4. The Eaton’s method used in this research uses sonic log as data source.